Patterns of Coronary Dominance in Patients undergoing Coronary Angiography - Khatun, Sanzida; Nepal, Rajesh; Yadav, Ranjeet Kumar (Birat Journal of Health Sciences, 2020)
Introduction: Right and left coronary arteries supply the heart. The dominant vessel supplies posterior descending artery and at least one posterolateral branch to inferior surface of heart. The coronary circulation can be: right dominant, left dominant and co-dominant. Objectives: The aim of this study was to determine the different patterns of coronary artery dominance in patients with coronary artery disease. Methodology: A descriptive cross-sectional study was conducted in patients undergoing coronary angiography in cathlab of Nobel Medical College and Teaching Hospital, Biratnagar, Nepal. The coronary angiography was taken from all standard views. For assessing the left dominance, left anterior oblique cranial view was specially focused. Results: There were 72.9% right dominant, 22.2% left dominant and 4.9% co-dominant cases. Both sexes had similar patterns of coronary dominance (73.8% RD, 22.2% LD and 4.0% CD among males whereas, 71.4% RD, 22.1% LD and 6.5% CD among females) as that in total study population. The highest number of patients was found in 60 to 69 years of age group. More number of patients had left dominance in less than 50 years age group than in 50 years and above group. There were no significant differences in pattern of coronary dominance with age groups. Conclusion: The most prevalent type of coronary artery dominance is right dominance followed by left dominance and co-dominance.